An Analysis of Students’ Speaking Anxiety: A Case Study of 8th Grade Students at SMP Negeri 1 Bangli - Luh Made Intan Lestari; Putu Santi Oktarina; Ni Ketut Riska Dewi Prawita (Indo Publishing, 2026)
Speaking anxiety is a common psychological barrier that hinders students from performing well in oral communication, particularly in foreign language learning contexts. This study aimed to analyze the levels of speaking anxiety experienced by eighth-grade students at SMP Negeri 1 Bangli and to identify the contributing factors as well as the dominant factor of their speaking anxiety. A mixed-method approach with a case study design was employed, involving 70 students from classes VIII B and VIII C as the subjects. Data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the interactive model by Miles et al. (2014). The findings revealed that the majority of students experienced speaking anxiety at mild to high levels, with 28 students (40%) in the Anxious category, 26 students (37.1%) in the Mildly Anxious category, and 15 students (21.4%) in the Very Anxious category. Only one student (1.4%) was classified as Relaxed, and none were Very Relaxed. The dominant factors contributing to speaking anxiety were Communication Apprehension (70%) and Fear of Negative Evaluation (69.7%). Internal factors identified included limited vocabulary, fear of making mistakes, and lack of confidence, while external factors included being asked to speak without preparation, fear of being laughed at by friends, and pressure from teachers. This study confirms that speaking anxiety is a prevalent phenomenon among Indonesian junior high school students and aligns with the theory of foreign language anxiety proposed by Horwitz et al. (1986).